Shifts in soil biodiversity—A forensic comparison between Sus scrofa domesticus and vegetation decomposition. Issue 6 (December 2015) - Olakanye, Ayodeji O.; Thompson, Tim; Ralebitso-Senior, T. Komang
Abstract: In a forensic context, microbial-mediated cadaver decomposition and nutrient recycling cannot be overlooked. As a result, forensic ecogenomics research has intensified to gain a better understanding of cadaver/soil ecology interactions as a powerful potential tool for forensic practitioners. For this study, domestic pig ( Sus scrofa domesticus ) (4 g) and grass ( Agrostis / Festuca spp) cuttings (4 g) were buried (July 2013 to July 2014) in sandy clay loam (80 g) triplicates in sealed microcosms (127 ml; 50 × 70 cm) with parallel soil only controls. The effects of the two carbon sources were determined by monitoring key environmental factors and changes in soil bacterial (16S rRNA gene) and fungal (18S rRNA gene) biodiversity. Soil pH changes showed statistically significant differences ( p < 0.05) between the treatments. The measured ecological diversity indices (Shannon–Wiener, HꞋ ; Simpson, D ; and richness, S ) of the 16S rRNA and 18S rRNA gene profiles also revealed differences between the treatments, with bacterial and fungal community dominance recorded in the presence of S. scrofa domesticus and grass trimming decomposition, respectively. In contrast, no statistically significant difference in evenness ( p > 0.05) was observed between the treatments. Highlights: Significant differences in 16S Shannon–Wiener and Simpson diversity recorded for the control vs. two burial soils Distinct bacterial and fungal rRNA gene profile shifts for pig and grass soils, respectively Temporal divergence in burial soils observed after Tukey (HSD)/Bonferroni post hoc tests Potential applicability determined by sequencing and in situ studies